Marx and history: the Russian road and the myth of historical determinism - Pires, Guilherme Nunes (Ciências sociais UNISINOS, 2021)
This paper aims to point out the limits of the historical determinism thesis in Marx’s thought by analyzing his writings on the Russian issue and the possibility of a “Russian road” to socialism. The perspective of historical determinism implies that Marx’s thought is supported by a unilinear view of social evolution, i.e. history is understood as a succession of modes of production and their internal relations inexorably leading to a classless society. We argue that in letters and drafts on the Russian issue, Marx opposes to any attempt associate his thought with a deterministic conception of history. It is pointed out that Marx’s contact with the Russian populists in the 1880s provides textual elements allowing to impose limits on the idea of historical determinism and the unilinear perspective in the historical process.